Efficacy of standardized tracheostomy training with a simulation model for healthcare providers: A study by ISPAT team - ERDEM ERALP, ELA; KIYAN, GÜRSU; AY, NADİYE PINAR; GÖKDEMİR, YASEMİN (WILEY, 2022)
Introduction Tracheostomy care in children may be challenging, due to lack of knowledge of healthcare providers (HCPs). The aim of this study was to determine the level of knowledge of HCP who follow patients with tracheostomy and to increase this level with theoretical training and training in a simulation laboratory. Materials and Methods ISPAT (IStanbul PAediatric Tracheostomy), a multidisciplinary team for tracheostomy care was established and a training program was prepared. Participants were subjected to theoretical and practical pretests which evaluated their knowledge levels and skills for care, follow-up, and treatment of a patient with tracheostomy. After the theoretical and practical training given to the participants with a simulation model, theoretical and practical posttests were applied. Results Fifty-one HCP from nine tertiary pediatric clinics in Istanbul were enrolled in the training program. Only six (11.8%) of them had received standardized training programs previously. Regarding the theoretical tests, seven of the 33 questions were indicated as essential. The knowledge level of the participants based on the essential questions significantly increased after the training (p < 0.05 for all of the essential questions). The total number of correct answers and correct answers of three subheadings also significantly increased after the practical training (p < 0.001 for all). Ninety-five percent of the participants assessed the course as good or excellent in general. Conclusion Training in a simulation laboratory in combination with theoretical education can improve the knowledge and skills of the HCP enabling improved care of children with a tracheostomy.
Keywords: pulmonology (general); respiratory technology; PEDIATRIC TRACHEOSTOMY; MANAGEMENT-SKILLS; TRACHEOTOMY; EDUCATION; COMPLICATIONS; EXPERIENCE; KNOWLEDGE; VALIDATION; CAREGIVERS; IMPROVE